Synthesis and evaluation of antifungal properties of a series of the novel 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and its analogues - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Kumari, Ratna; Bhat, Manoj Kumar; Deshpande, Mukund V.; Srinivasan, Kumar V. (Bioorganic & Medicinal Chemistry, 2007)
A series of 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and various analogues have been synthesized in excellent isolated yields starting from various arylidenemalononitrile and 3-amino-2-cyclohexen-1-one in 1-propanol as solvent at reflux temperature in the absence of any added catalyst. All the synthesized compounds were evaluated for their antifungal activity. The relationship between functional group variation and biological activity of the evaluated compounds is discussed in the article. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; antiproliferative activity; arylidenemalononitriles; arylquinoline carbonitrile; Michael addition

Efficient synthesis of antifungal pyrimidines via palladium catalyzed Suzuki/Sonogashira cross-coupling reaction from Biginelli 3,4-dihydropyrimidin-2(1H)-ones - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Deshpande, Mukund V.; Srinivasan, Kumar V. (Tetrahedron, 2008)
An efficient regioselective approach to the synthesis of tetrasubstituted pyrimidines was developed by sequential functionalization of easily available Biginelli 3,4-dihydropyrimidine-2(1H)-ones via dehydrogenation, chlorination followed by palladium catalyzed C-C Suzuki/Sonogashira coupling reaction. All the synthesized compounds were evaluated in vitro for their antifungal activities against Candida albicans, Cryptococcus neoformans, Benjaminiella poitrasii, Yarrowia lipolytica, and Fusarium oxysporum, and antibacterial activities against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activities; Biginelli compounds; chlorination; Oxidation; Pyrimidines; Suzuki coupling